1964
DOI: 10.1088/0029-5515/4/4/012
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a high-beta plasma produced by electron-cyclotron heating

Abstract: The sequence of experiments resulting in the development of steady-state dense hot-electron plasmas is briefly described. These plasmas are produced in magnetic-mirror machines by radiation at the electron-cyclotron frequency. The electron-cyclotron plasma with the greatest stored energy to date has a volume of ∼ 50 liters, an electron “temperature” of 120 keV, a density of 4 — 7 × 1011/cm3, an d an average beta of ∼ 0.4. This plasma is created in the EPA Facility by a 50-kW c.w. 10.6-gHz microwave power sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1966
1966
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…2,3 Electrons which are not in phase with the accelerating field will be lost to the walls, or will contribute to the cold plasma electron distribution to satisfy the charge equilibrium within the plasma: n e = ͚ k=1 max Z k n i . For electron cyclotron resonance ion source ͑ECRIS͒, the electron density inside the plasma chamber is in the range of 10 12 -10 14 cm −3 , estimated with the magnetic flux density which corresponds to the cutoff density, 1 n e = ͉B ͉ · 0 / m e .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Electrons which are not in phase with the accelerating field will be lost to the walls, or will contribute to the cold plasma electron distribution to satisfy the charge equilibrium within the plasma: n e = ͚ k=1 max Z k n i . For electron cyclotron resonance ion source ͑ECRIS͒, the electron density inside the plasma chamber is in the range of 10 12 -10 14 cm −3 , estimated with the magnetic flux density which corresponds to the cutoff density, 1 n e = ͉B ͉ · 0 / m e .…”
Section: Introductionmentioning
confidence: 99%
“…(9): S•K·n .V (12) The FAD has an output for each beam component; full, half and third energy, and each channel is calibrated separately. Equation (12) is then solved in each case for the calibration constant, K, which contains the desired calibration information: Kl = 2.88 x 10-16 volt -sec/ion (full energy) K2 = 6.85 x 10-17 (1/2 energy) KJ = 1.93 x [10][11][12][13][14][15][16] (1/3 energy).…”
Section: Fast Atom Detectormentioning
confidence: 99%
“…Past experience (Refs. [13][14][15][16][17] has shown that electron cyclotron resonance heating (ECRH) is a viable technique for producing hot, mirror confined electrons.…”
mentioning
confidence: 99%
“…Nevertheless #~0.5 appears to be an experimental upper limit for the density of the energetic electrons in well-confined neutral plasmas. 7 FIG. I.…”
Section: Cp W -Cp{z)_n E {Z)-zn I {Z)mentioning
confidence: 99%
“…Experiments on the minimum-B geometry Interem device at'Oak'Ridge National Laboratory, 8 happily, indicate magnetohydrodynamic stability of a hot electron plasma with a reduced density of cold plasma background. The required microwave source power will be best determined by experiment; Dandl et al 7 consistently obtained hot electron ECRH (electron cyclotron-resonance heated) plasmas with microwave generators in the range 1-50 kW. Unique to the proposed stripped-ion source, however, is the need to maintain the space potential of the mirror-confined hot electron plasma at a negative value which is considerably larger in magnitude than the classical ambipolar potential, 9 Electron injection is therefore demanded and the need to overcome the repulsive negative potential in fact requires injection from an electron gun.…”
Section: (N)[b(z Ni )-B(z O )]>E[(p"-cpmentioning
confidence: 99%